Bipolar Voltage Mapping for the Evaluation of Atrial Substrate: Can We Overcome the Challenge of Directionality? - Yamaguchi, Takanori (J Atr Fibrillation, 2019)
The relationship between atrial fibrosis and atrial fibrillation (AF) has been proven. Patient specific substrate ablation targeting fibrotic tissue estimated by bipolar voltage mapping has emerged as an alternative strategy for additional substrate modification beyond pulmonary vein isolation. The primary mechanism of a low-voltage electrogram has been suggested to be atrial fibrosis, however, no direct correlation between histological fibrosis and low-voltage zone has been confirmed. Furthermore, the definition of low-voltage zone is still controversial, and bipolar voltage amplitudes depend on multiple variables including electrodes orientation relative to direction of wavefront, electrode length, interelectrode spacing, and tissue contact. The aim of this article is to review the role and limitation of voltage mapping, and to share our initial experience of a newly released grid-pattern designed mapping catheter to make the voltage mapping more reliable to guide patient specific AF ablation.